Impact of Enterococcus faecalis Endocarditis Treatment on Risk of Relapse. (19th September 2022) - Danneels, Pierre; Hamel, Jean-François; Picard, Léa; Rezig, Schéhérazade; Martinet, Pauline; Lorleac'h, Aurélien; Talarmin, Jean-Philippe; Buzelé, Rodolphe; Guimard, Thomas; Le Moal, Gwenaël; Brochard-Libois, Julia; Beaudron, Aurélie; et al.
Abstract: Background: Enterococcus faecalis infective endocarditis (EFIE) is characterized by a higher frequency of relapses than other infective endocarditis. The role of the treatment on its occurrence remains poorly understood. The aim of this study was to investigate whether the antibiotic regimen could impact the risk of relapse in EFIE. Materials: This was a multicenter retrospective study of patients diagnosed with definite EFIE between 2015 and 2019 in 14 French hospitals. The primary endpoint was the occurrence of relapses within the year following endocarditis diagnosis. As death was a competing risk for relapse, Fine and Gray models were used for studying risk factors and impact of treatment. Results: Of the 279 patients included, 83 (29.7%) received the amoxicillin-gentamicin (A-G) combination, 114 (40.9%) amoxicillin-ceftriaxone (A-C), 63 (22.6%) A-G and A-C (A-G/A-C) sequentially, 9 (3.2%) amoxicillin (A), and 10 received other treatments. One-year-relapse rate was 9.3% (26 patients). Relapse occurred after a median delay of 107 days from EFIE diagnosis; 6 occurred after 6 months, and 6 were diagnosed by blood cultures in asymptomatic patients. In multivariate analysis, surgery during treatment was a protective factor against one-year relapse and death. The cumulative incidence of relapse 1 year after endocarditis was 46.2% for patients treated with amoxicillin, 13.4% with A-G, 14.7% with A-C, and 4.3% with A-G/A-C ( P ≥.05 in multivariate analysis). Conclusions: Relapses after treatment of EFIE are frequent, frequently asymptomatic, and may occur more than 6 months after the initial episode. Abstract : This retrospective multicentric study of 279 Enterococcus faecalis endocarditis illustrates that relapses are frequent (1-year rate 9.3%) and can occur more than 1 year after the initial episode. Cardiac surgery and antibiotic combination are cornerstones of treatment to prevent relapse.